Investigation of soils of stubbles of winter wheat and winter peas in conventional and reduced tillage systems - Tuba, Géza; Kovács, Györgyi; Zsembeli, József (Acta Agraria Debreceniensis, 2016)
The effect of reduced and conventional tillage on soil compaction, soil moisture status and carbon-dioxide emission of the soil was studied on a meadow chernozem soil with high clay content in the soil cultivation experiment started in 1997 at Karcag Research Institute. Our investigations were done on stubbles after the harvest of winter wheat and winter peas after the very droughty vegetation period of 2014/2015. We established that the soil in both tillage systems was dry and compacted and the CO2-emission was very low. The positive effects of reduced tillage could be figured out only in the soil layer of 40–60 cm in the given weather conditions of that period.